Desenvolvimento de novas associações farmacêuticas a base de 5- fluorouracil com vistas à aplicação no tratamento de câncer de pele. - FERREIRA, Elis Cristina de Sousa (2023)
Cancer is a center of several diseases, according to the National Cancer Institute, where cancer cells multiply, gaining space from cells considered good, invading organs and tissues causing cancer itself. Faced with the various types of cancer most incident in the world, such as colorectal, breast, pancreas, head and neck, prostate, uterine cervix, colon and rectum and melanoma skin, traditional treatments are the most used, including surgery, chemotherapy and radiotherapy. In these treatments, 5-Fluorouracil, 5-FU, is one of the most used drugs for different types of cancer. Its continuous use causes several side effects in addition to being rapidly eliminated and having a short plasma half-life. In order to improve its side effects and intensify its action in the treatment of cancer, resorcin was used to prepare associations, which can be used for various purposes, such as contributing to the ability to improve the stability of vitamin D, UV stabilizers, having pharmacological properties which include treatments for the skin. These associations were characterized by FTIR where it was possible to predict the possible interactions between both drugs, while the XRD helped to investigate the crystallinity of the associations. As carriers of the synthesized associations, a biopolymeric matrix of chitosan and gelatin was used, which were processed as homogeneous films with good mechanical properties. Such films were characterized by SEM, in addition to stability, water absorption, transparency and UV light blocking tests, where they were shown to be transparent in visible light and blockers in UV light.